2022
DOI: 10.7759/cureus.21570
|View full text |Cite
|
Sign up to set email alerts
|

Snakebites in Pediatric Patients in Kahramanmaraş: Is Pro-brain Natriuretic Peptide a Prognostic Biomarker for Snakebites?

Abstract: Background: Snake envenomations are a serious cause of mortality and morbidity in the world.Aims: This study was conducted to investigate snake bites in pediatric patients in Kahramanmaraş and to determine whether pro-brain natriuretic peptide (proBNP) has a prognostic value in these patients.Methods: Pediatric patients aged <18 years who presented to the pediatric emergency department with snakebites were reviewed retrospectively. The demographical, clinical, laboratory, treatments, and outcomes data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…In another study conducted in adult patients with CO poisoning, NT-proBNP > 100 pg/mL at admission was found to be a significant marker in predicting left ventricular dysfunction [ 28 ]. In our previous studies, we reported the prognostic value of proBNP in various poisonings such as snake bites and scorpion bites [ 29 , 30 ]. We also showed that it was predictive of cardiac involvement in children with COVID-19 at the time of admission [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted in adult patients with CO poisoning, NT-proBNP > 100 pg/mL at admission was found to be a significant marker in predicting left ventricular dysfunction [ 28 ]. In our previous studies, we reported the prognostic value of proBNP in various poisonings such as snake bites and scorpion bites [ 29 , 30 ]. We also showed that it was predictive of cardiac involvement in children with COVID-19 at the time of admission [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a few months later, he complained about hyperalgesia, swelling, alternating cool and warm sensation, and dermal changes, and was then diagnosed with complex regional pain syndrome (CRPS), which is a rare case reported by snakebites in the world [ 59 ]. In addition, two cases of pediatric CRPS (<18-year-old) were reported to be bitten by a viper and southern Pacific rattlesnake in Turkey [ 62 ] and the US [ 63 ], respectively.…”
Section: Envenoming By Rear-fanged Snakesmentioning
confidence: 99%